Pendampingan Perumusan Penggunaan Nomenklatur “Putusan” Jenis Produk Hukum MPR RI - Syamsul, E. Mulya (Ma'soem University, 2023)
The purpose of this service activity is to analyze whether the MPR's authority over the form of